CREATING PLACES OF IDENTITY AND SOCIAL INTERACTION: EXAMINING THE RELATIONSHIP BETWEEN TRANSIT-ORIENTED DEVELOPMENT AND PLACE MAKING - Nursanty, Eko (Unika Santo Thomas, 2023)
This qualitative literature study explores the synergistic relationship between Transit-Oriented Development (TOD) and Place Making in shaping urban environments that nurture strong identities and vibrant social interactions. Drawing from a wide range of literature sources, including journals, books, reports, and policy documents, the study conducts a thematic analysis of the existing body of research concerning the TOD-Place Making nexus. The findings emphasize that TOD has substantial potential for cultivating places with distinct identities and fostering social interactions within urban areas. Place Making emerges as a pivotal strategy for designing spaces that promote local identities, community engagement, and high-quality public realms. The study concludes that the integration of TOD and Place Making can metamorphose transportation hubs into lively centers of social life and community activities. However, challenges such as regulatory hurdles, stakeholder coordination, and long-term sustainability require attention. This research advances our comprehension of crafting and managing sustainable urban environments, offering insights for planning guidelines and policies. Particularly relevant to Indonesian cities, embracing TOD and Place Making principles can create inclusive, livable settings that amplify local identities and community cohesion, guiding urban planning and policy decisions for the sustainable evolution of Indonesian cities.